Botulinum toxin treatment for hypersalivation in anti‐NMDA receptor encephalitis. Issue 11 (26th September 2017) - Jun, Jin‐Sun; Seo, Han Gil; Lee, Soon‐Tae; Chu, Kon; Lee, Sang Kun
Abstract: Hypersalivation is one of the intractable symptoms of anti‐ N ‐methyl‐d ‐aspartate receptor (NMDAR) encephalitis. While anticholinergic medications partially improve the hypersalivation, they can aggravate the autonomic dysfunctions associated with anti‐NMDAR encephalitis. Thus, we investigated the efficacy and safety of botulinum toxin type A injection on hypersalivation refractory to anticholinergics in six patients with anti‐NMDAR encephalitis. Hypersalivation was well‐controlled without remarkable adverse reaction over 16 weeks after botulinum toxin type A, although two patients were reinjected at 12 weeks due to reaggravation of hypersalivation. Our findings suggest that botulinum toxin type A might be a better choice than anticholinergics for management of hypersalivation in patients with anti‐NMDAR encephalitis.